Model Pengembangan “Diet Media TV” Sebagai Penangkal Kecanduan Anak Terhadap Media TV dan Dampak Negatifnya - SURATNOAJI, MSI, DR. CATUR (Jurnal Ilmu Komunikasi, 2010)
YPMA research in Indonesia showed that most Indonesia children watch TV much longer than school hours. Activities watching TV besides make  a child addicted to TV can also interfere with studi hours at home. In an  attempt to solve the problem of children watching TV is an necessary of research on “TV media diet” that can  reduce the nagative impact of TV media. Research done in the city Surabaya in East Java Province by using qualitative methods. Informant research is the mothers who have children of primary school. Data collection techniques performed by  method of in-dept interviews. Results showed that children in watching TV on the push to find information and entertainment.Time children spent in watching TV more than two hours and this can be categorized as TV addiction. Activities of watching TV after school activities and this is often interfere with the hours of home study. Parent do not active in mentoring children in watching television. Parent tend to free the child to select TV programming without any selection of parent. TV programming selected children tend not to quality so not good for the child’s personality development. Research has developed a formula “TV media diet” in effort to prevent child addcited to TV. Formula “TV media diet” developed by : 1) limiting activities of children watch TV in maximum of 2 hours; 2) create parameters that can measure whether children addicted to TV or not;  3) create a parameter that can control what children watch TV programs are qualified or not; 4) mentoring children in watching TV; 5)  balancing the need of children in watching TV with other activities.